O desenho infantil no contexto de aulas remotas em escolas de educação infantil no município de São Francisco do Conde – Ba - Santos, Nataly Ferreira Costa dos (2022)
A common practice among children who are the target audience of Early Childhood Education, drawing helps the child to develop both creative and innovative capacity as well as visual-motor skills, among other aspects. From this premise, to understand how children's drawing has been worked and developed in classes and remote activities in early childhood schools in the city of São Francisco do Conde, Bahia. And, to achieve this answer, I list as specific objectives: 1. identify the importance of children's drawing; 2. situate the implementation of early childhood education and its historical context; 3. expand knowledge about Emergency Remote Teaching (ERE); 4. analyze how early childhood teachers have stimulated the practice of drawing in classes and remote activities; and 5. to reflect on the impacts of the pandemic on the graphic and creative development of early childhood education students according to the speeches of the research subjects, the early childhood education teachers in the municipality of São Francisco do Conde, Bahia. I chose the inductive method (empiricist) to approach this research, because it considers knowledge from experience and/or observation of particular data. From the point of view of its objective, it is an exploratory research, as it aims to provide more information on the subject investigated here. I use a qualitative approach and for data analysis, I use the content analysis technique, according to Bardin (1977), with emphasis on thematic analysis, which occurs in three phases: pre-analysis, material exploration, and treatment of results. As for the technical procedures, it is a field research. The questionnaire, more specifically, the Google Form (Forms) was the instrument for collecting and producing data chosen for this research, because, as it is a virtual instrument, it facilitates a greater reach of people, in this case, the research subjects, making Thus, it is an instrument of great relevance for this research, and in view of the practicality of this instrument for collecting and producing data, I chose to have it composed of open questions, allowing the research participants to put themselves in the written text. of this research are public daycare centers (03) and preschools (07) in the municipality of São Francisco do Conde, a city in the Recôncavo region of Bahia. The research subjects are ten teachers from different kindergarten schools who work in the central urban area, peripheral urban area (a little far from the center) and, in the rural area of ​​the municipality, who answered four questionnaires, namely : Initial Information; Informative Questionnaire; Reflective Questionnaire and Final Questionnaire. One of the results identified in the research was the fact that the children's drawing was indeed encouraged by the teachers and developed by the students in the midst of Emergency Remote Teaching (ERE), the teachers' design was also highlighted and how it was encouraged in their planning and teaching plans for the classes developed, also highlighting the challenges of this incentive to the act of designing in the ERE, as well as criticism of the neglect that government officials have expressed towards public education, exempting themselves from the responsibility of guaranteeing this, which is a constitutional right. of all Brazilians, education. This research ends by demonstrating that children's drawing is present in the ERE through the teaching incentive that understands that this is a pedagogical instrument capable of contributing to the development of students during the Covid-19 pandemic.